Bilateral toxoplasma retinitis with vitreous hemorrhage and macular edema during immunosuppressive treatment - Lasota, Piotr (Klinika Oczna / Acta Ophthalmologica Polonica, 2025)
A 54-year-old woman with a history of peripheral spondyloarthropathy for 10 years, treated with steroids and methotrexate, was hospitalized due to necrotic retinitis with arteritis of left eye. Right eye was thought to have self-healing toxoplasma retinitis one year earlier. Different opportunistic infections, including toxoplasma, cytomegalovirus and herpes zoster virus, were considered. Discontinuation of methotrexate and treatment against toxoplasmosis including intravitreal clindamycin stopped the infection. During the follow-up period massive retinal neovascularization, vitreous hemorrhage and macular edema occurred despite panretinal laser photocoagulation. After spontaneous posterior vitreous detachment, anti-VEGF injections were performed to improve visual acuity by reduction of macular edema and resolution of vitreous hemorrhage. At the last follow-up visit, 18 months after presentation, visual acuity was 0,1 (Snellen).